Real-time measurement of the intracellular pH of yeast cells during glucose metabolism using ratiometric fluorescent nanosensors - Elsutohy, Mohamed M.; Chauhan, Veeren M.; Markus, Robert; Kyyaly, Mohammed Aref; Tendler, Saul J.B.; Aylott, Jonathan W. (Royal Society of Chemistry, 2017)
Intracellular pH is a key parameter that influences many biochemical and metabolic pathways that can also be used as an indirect marker to monitor metabolic and intracellular processes. Herein, we utilise ratiometric fluorescent pH-sensitive nanosensors with an extended dynamic pH range to measure the intracellular pH of yeast (Saccharomyces cerevisiae) during glucose metabolism in real-time. Ratiometric fluorescent pH-sensitive nanosensors consisting of a polyacrylamide nanoparticle matrix covalently linked to two pH-sensitive fluorophores, Oregon green (OG) and 5(6)carboxyfluorescein (FAM), and a reference pH-insensitive fluorophore, 5(6)carboxytetramethylrhodamine (TAMRA), were synthesised. Nanosensors were functionalised with acrylamidopropyltrimethyl ammonium hydrochloride (ACTA) to confer a positive charge to the nanoparticle surfaces that facilitated nanosensor delivery to yeast cells, negating the need to use stress inducing techniques. The results showed that under glucose-starved conditions the intracellular pH of yeast population (n ≈ 200) was 4.67 ± 0.15. Upon addition of D-(+)-glucose (10 mM), this pH value decreased to pH 3.86 ± 0.13 over a period of 10 minutes followed by a gradual rise to a maximal pH of 5.21 ± 0.26, 25 minutes after glucose addition. 45 minutes after the addition of glucose, the intracellular pH of yeast cells returned to that of the glucose starved conditions. This study advances our understanding of the interplay between glucose metabolism and pH regulation in yeast cells, and indicates that the intracellular pH homestasis in yeast is highly regulated and demonstrates the utility of nanosensors for real-time intracellular pH measurements.